MISUSE OF KISWAHILI NOUN CLASS MARKERS IN KENYA: ILLUSTRATION WITH THE CASE OF THE KISWAHILI OF FORM-THREE STUDENTS OF THE AKIBA SECONDARY SCHOOL IN NAIROBI (The University of Nairobi Journal of Language and Linguistics, 2023)
The aim of this paper was to establish the extent of misuse of noun classmarkers in written Kiswahili in Kenya. It illustrates with the case of theKiswahili of Form Three students of the Akiba Secondary School in Nairobi. Asample of thirty of them was used in the study: 15 male and 15 female. Ittested the following hypotheses: (i) The Form Three students of the AkibaSecondary School will make more mistakes in the use of noun class markersreserved for the the I-ZI noun class—as would be used for the pair of nounssahani (plate) in the singular and sahani (plates) in the plural—than in the useof those reserved for other noun classes. (ii) The male students will make moremistakes in the use of Kiswahili noun class markers than their femaleclassmates. A questionnaire consisting of sentences testing the respondents’ability to correctly use the various noun class markers was used. The frequencyof correct uses of individual noun class markers by all the thirty respondentswas reported in a table, as was the total performance on each one of the nounclass markers by all the students. The results show that contrary to what thestudy had hypothesized, it was the A–WA noun class markers (as illustrated bythe bold-type morphemes in the pair of sentences Kipepeo anaruka akituamgombani (The butterfly is flying and landing on a banana trunk) and Vipepeowanaruka wakitua migombani (The butterflies are flying and landing on abanana trunk), and not the I-ZI noun class markers, that turned out to be themost frequently misused by the respondents. The second hypothesis was notstatistically confirmed either: although the mean for the female students wasindeed higher than that for the male in terms of percentages, a t-test foundthat the difference was not statistically significant.